2017
DOI: 10.1021/acs.biomac.7b00590
|View full text |Cite
|
Sign up to set email alerts
|

Nontransformed and Cancer Cells Can Utilize Different Endocytic Pathways To Internalize Dendritic Nanoparticle Variants: Implications on Nanocarrier Design

Abstract: Three hyperbranched polyglycerol nanoparticle (HPG NP) variants were synthesized and fluorescently labeled for the study of their cellular interactions. The polymeric nanoparticle that contains a hydrophobic core and a hydrophilic HPG shell, HPG-C-HPG, is taken up faster by HT-29 cancer cells than nontransformed cells, while similar uptake rates are observed with both cell types for the nanoparticle HPG-C-PEG that contains a hydrophobic core and a polyethylene glycol shell. The nanoparticle HPG-104, containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…30 Thus, we researched whether the cellular uptake of NP was influenced by the temperature. The cellular uptake of NP in the HepG2 cells incubated at 4°C was decreased ~74.1% (Figure S1), suggesting that the HA-Se-PEI@siRNA NP was internalized into the cells in an energy-dependent manner.…”
Section: Cellular Uptake Of Npmentioning
confidence: 99%
“…30 Thus, we researched whether the cellular uptake of NP was influenced by the temperature. The cellular uptake of NP in the HepG2 cells incubated at 4°C was decreased ~74.1% (Figure S1), suggesting that the HA-Se-PEI@siRNA NP was internalized into the cells in an energy-dependent manner.…”
Section: Cellular Uptake Of Npmentioning
confidence: 99%
“…To investigate the mechanism involved in the cellular uptake of DTNPs, we first incubated HeLa cells with 20 mm DTNPs at 4 8Cf or 2h.I nterestingly,t here was little difference in intracellular fluorescence compared with that at 37 8C, suggesting that the uptake of DTNPs was not energy-dependent ( Figure S16). We then pretreated HeLa cellswith different endocytosis inhibitors, such as chlorpromazine (CPZ), [20] Filipin III, [21] and 5-(Nethyl-N-isopropyl) amiloride (EIPA), [22] which also hadl ittle effect on the intracellular fluorescence( Figure S17). These results suggested that the intracellular delivery of DTNPs did not rely on the endocytosis/phagocytosis pathway.F urthermore, HPLC analysis of both culture medium and lysed HeLa cells following incubation with 20 mm DTNPsf or 2h showedt hat the majority of cationic DH-BBR + was taken up by HeLa cells, while the anionic TPB À wasd istributed mainly extracellularly ( Figure S18).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the mechanism involved in the cellular uptake of DTNPs, we first incubated HeLa cells with 20 μ m DTNPs at 4 °C for 2 h. Interestingly, there was little difference in intracellular fluorescence compared with that at 37 °C, suggesting that the uptake of DTNPs was not energy‐dependent (Figure S16). We then pretreated HeLa cells with different endocytosis inhibitors, such as chlorpromazine (CPZ), Filipin III, and 5‐( N ‐ethyl‐ N ‐isopropyl) amiloride (EIPA), which also had little effect on the intracellular fluorescence (Figure S17). These results suggested that the intracellular delivery of DTNPs did not rely on the endocytosis/phagocytosis pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Gating of the live target cells was performed by selecting the main cell populations in the forward and side scatter profiles. Normalized mean florescence was computed by subtracting of the geometric mean florescence of the cells that were not incubated with any florescence labels [37].…”
Section: Methodsmentioning
confidence: 99%